(untitled) (Research, Society and Development, 2020)
Biodigesters have been studied and improved in an accelerated way in the last decade. The concern to change the world energy matrix, giving priority to the forms of clean energy and leaving aside the use of fossil fuels, puts the use of biogas for energy generation as an attractive alternative. In addition to being a form of clean energy, it is also able to prevent compounds harmful to the ecosystem such as methane, carbon dioxide and hydrogen sulphide from being released into the atmosphere. The objective of that research is to present an updated bibliographic survey on the technology used in biodigesters and the factors that directly influence the production of biogas. After the bibliographic analysis, it was possible to identify that through the correct reading, analysis and control of pH, temperature, hydraulic retention time, amount of nutrients and water in the system and the organic matter agitation process inside the reactor it is possible to obtain a greater amount of biogas, including better quality. What determines the quality of the biogas is the amount of methane gas in the composition, as it is the methane that will be used for burning.